2010
DOI: 10.1371/journal.pone.0013468
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Mediated Gene Delivery in Adult GM1-Gangliosidosis Mice Corrects Lysosomal Storage in CNS and Improves Survival

Abstract: BackgroundGM1-gangliosidosis is a glycosphingolipid (GSL) lysosomal storage disease caused by a genetic deficiency of acid β-galactosidase (βgal), which results in the accumulation of GM1-ganglioside and its asialo-form (GA1) primarily in the CNS. Age of onset ranges from infancy to adulthood, and excessive ganglioside accumulation produces progressive neurodegeneration and psychomotor retardation in humans. Currently, there are no effective therapies for the treatment of GM1-gangliosidosis.Methodology/Princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 55 publications
(102 reference statements)
3
80
1
Order By: Relevance
“…Vectors expressing the defi cient enzymes needed for corresponding ganglioside degradation are delivered intracranially. AAV treatments can successfully restore the defi cient enzymatic activity and eliminate most of the corresponding ganglioside storage ( 42,43,68 ). We observed that AAV treatment also eliminated secondary storage of BMP in SD mouse brains.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Vectors expressing the defi cient enzymes needed for corresponding ganglioside degradation are delivered intracranially. AAV treatments can successfully restore the defi cient enzymatic activity and eliminate most of the corresponding ganglioside storage ( 42,43,68 ). We observed that AAV treatment also eliminated secondary storage of BMP in SD mouse brains.…”
Section: Discussionmentioning
confidence: 61%
“…These fi ndings suggest that BMP storage is not likely associated with infl ammation, but is associated with ganglioside storage. AAV gene therapy has been successfully used to treat GM1 and GM2 gangliosidosis in both mice and cats ( 42,43,68 ). Vectors expressing the defi cient enzymes needed for corresponding ganglioside degradation are delivered intracranially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adeno-associated virus (AAV) vector system offers important advantages as a gene delivery tool for treating a great variety of diseases, including a broad tissue tropism and absence of known pathogenesis in humans (Berns and Linden, 1995). Recombinant AAV (rAAV) vectors based on AAV serotype 2 (AAV2) have been shown to transduce both neuronal and nonneuronal cells in the CNS in numerous gene therapy studies, with demonstrated therapeutic benefits in treating neurological diseases (Daya and Berns, 2008), including MPS and other LSDs, in animal models (Fu et al, 2002(Fu et al, , 2003(Fu et al, , 2007(Fu et al, , 2011Heuer et al, 2002;Desmaris et al, 2004;Liu et al, 2005;Fraldi et al, 2007;Sands and Haskins, 2008;McCarty et al, 2009;Baek et al, 2010;Heldermon et al, 2010;Ruzo et al, 2012). Multiple phase I clinical trials have been completed using rAAV gene delivery approaches in patients with neurological disorders (McPhee et al, 2006;Kaplitt et al, 2007;Worgall et al, 2008;Marks et al, 2010;Mittermeyer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison with AAV gene delivery to brain is difficult to establish as the resulting level of enzyme activity in different brain regions is measured in tissue blocks where the vast majority of cells are not transduced. Therefore the reported enzymatic activities of 10-to 100-fold above normal in different mouse [123,135] and cat [126,136] models of LSDs represent the activity of enzyme that is distributed throughout the brain from the target sites and now resides in non-transduced cells. Presently, there is no information on the degree of overexpression that takes place in AAV transduced cells in the target structures.…”
Section: Challengesmentioning
confidence: 99%